Hematopoietic Dysfunction during Graft-Versus-Host Disease: A Self-Destructive Process? - Konradin F. Müskens; Caroline A. Lindemans; Mirjam E. Belderbos (Cells, 2021)
Graft-versus-host disease (GvHD) is a major complication of allogeneic hematopoietic (stem) cell transplantation (HCT). Clinically, GvHD is associated with severe and long-lasting hematopoietic dysfunction, which may contribute to the high mortality of GvHD after HCT. During GvHD, excessive immune activation damages both hematopoietic stem and progenitor cells and their surrounding bone marrow niche, leading to a reduction in cell number and functionality of both compartments. Hematopoietic dysfunction can be further aggravated by the occurrence—and treatment—of HCT-associated complications. These include immune suppressive therapy, coinciding infections and their treatment, and changes in the microbiome. In this review, we provide a structured overview of GvHD-mediated hematopoietic dysfunction, including the targets in the bone marrow, the mechanisms of action and the effect of GvHD-related complications and their treatment. This information may aid in the identification of treatment options to improve hematopoietic function in patients, during and after GvHD.